THE IMPACT OF TECHNOLOGICALLY INDUCED TEXT- MESSAGES ON THE WRITTEN ENGLISH OF STUDENTS IN FORMAL CONTEXT: THE CASE OF ABU/SBRS STUDENTS - Jonah, Amodu Eneojoh (Sokoto Educational Review, 2020)
Technology is as much a part of our lives today in Nigeria as is communication. The combination of the two has changed the way Nigerian students send and receive messages. While technology has made the whole world smaller and even pedagogy easier, it has also created new set of problems in the teaching and learning of English as a second language thereby compounding the adverse situations that exist. This paper focuses on the effects that the technologically induced text-message has brought to bear in the written English of students. The essays written by students of ABU/SBRS Funtua under examination conditions are the source of data for this study. Findings reveal that, to a very large extent, text items used in informal contexts are beginning to find their way into the formal writing of Nigerian students. The paper advocates for a team and collaborative effort by all teachers irrespective of discipline in checking this menace. It further suggests that all teachers should see themselves first as teachers of English or else in the next few years, the written English of Nigerian students would definitely not withstand the demands of national and international standards for English language usage. This radical approach should also be strengthened by all examination bodies and institutions in Nigeria.